Fermentation of cigar tobacco leaves with citrus flavonoids: changes in chemical, microbiological, and sensory properties - Hu, Wanrong; Cai, Wen; Jia, Yun; Zhang, Qianying; Zhang, Zhengcheng; Wang, Yue; Sun, Chongde; Li, Dongliang (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Fermentation plays a significant role in improving the quality of cigar tobacco leaves. Particularly, fermentation with characteristic additives has been identified as an effective approach to enhance the fermentation process. The objective of this study was to develop new additives and investigate their influence on cigar tobacco leaves. Methods: The active ingredients extracted from three citrus species were obtained by ultrasonic-assisted extraction followed by solid phase purification. The effects of these ingredients as fermentation additives on the primary chemical components, microbial communities, and sensory quality of cigar tobacco leaves were subsequently analyzed. Results: Results showed that: (1) Flavonoids were the main components of the prepared citrus extracts. (2) The addition of citrus extracts resulted in a reduced content of amino acids, oxalic acid, and unsaturated fatty acids in cigar tobacco leaves, while increasing the content of citric acid. Besides, the total amount of aroma substances in cigar tobacco leaves increased by 38.15% with the addition of citrus extracts, with notable enhancements in the levels of D-limonene, β-dihydroionone, dihydroactiniolactone, and other representative aroma components. (3) The addition of citrus extracts promoted the succession of the microbial community in cigar tobacco leaves and promoted the enrichment of Pseudomonas and Corynebacterium. (4) The addition of citrus extracts effectively reduced the irritation and improved the aroma richness of cigar tobacco leaves. Discussion: In this study, the influence of citrus-derived active ingredients on cigar quality was systematically analyzed, providing a reference for the development of characteristic fermentation additives for cigars and the extension of cigar quality enhancement technologies.